A new spray current control for the reliable operation of a single-capillary electrospray. (November 2022) - Kang, Shipeng; Chen, Amelia B.; Yu, Tongzhu; Yang, Yixin; Gui, Huaqiao; Liu, Jianguo; Chen, Da-Ren
Abstract: Cone-jet electrospray has been proposed for various applications due to its ability to produce monodisperse droplets. The stable operation of the electrospray process is extremely important for quality assurance purposes, particularly for applications that require long-term operations. Typically, both the spray current and liquid meniscus shape are used to monitor the working condition of an electrospray. In practice, various factors (operational and environmental) could affect the electrospray operation. Thus, a new spray current control system was developed to improve the stability of a single capillary electrospray operated in the cone-jet mode. The new spray current control system has two control loops: the primary loop for spray current control and the auxiliary loop for meniscus image control. A simple method to characterize the shape of the liquid meniscus and to identify the operational mode of an electrospray was proposed and the performance of the proposed spray current control system was investigated. It was shown that, with the new control strategy, a single capillary electrospray system was able to continuously operate when encountering a severe perturbation (without the over-shooting caused by the previous control strategies) (i.e., the electrospray converged to the target spray current and liquid meniscus shape even when challenged by step perturbation on the spray liquid feeding flow rate). Highlights: A new strategy for the control of spray current in a single capillary electrospray is proposed. The strategy consists of both primary and axillary loops for spray current and liquid meniscus controls, respectively. A simple method to characterize the shape of liquid meniscus in the cone-jet mode is proposed. The performance of new control system was evaluated.